If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 52 = 3x Solving 52 = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 52 + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 52 + -3x = 0 Add '-52' to each side of the equation. 52 + -52 + -3x = 0 + -52 Combine like terms: 52 + -52 = 0 0 + -3x = 0 + -52 -3x = 0 + -52 Combine like terms: 0 + -52 = -52 -3x = -52 Divide each side by '-3'. x = 17.33333333 Simplifying x = 17.33333333
| -5(2+2q)=2(5+5q) | | 2(4)+4+4+2=2(4)+10 | | -195=x+5(9-5x) | | 2a-41=a+21 | | P=90-2(19) | | F(x)=6(x+8)-3 | | 7r=3r | | 11+2b=15 | | 3s-75=s+15 | | 3=11-2x-3x+5 | | P(19)=90-2(19) | | z+87=2z | | 16+2q=12 | | N=-2+x | | -5=12(6x-2)+7x | | s^2+(4s+3)=y | | P(19)=90-2x | | 15-2/5f=-6 | | 19.2j+3(17.3j+4.57)=3(9.8j-2.38) | | X=-2+n | | 14-(X+8)=8X-3 | | 408=-8(10n+9) | | (5-4i)(2+6i)=0 | | 10=z^2+3z | | 0.33(2x-1)=0.5(3x+1) | | g-62=15 | | 16+24=-5(3x-8) | | 6(2x+1)=2x-6x | | -13s-5+5s=11s+2(-11s-16) | | 312.50=a+.25 | | 3y^2+21y=0 | | n=4+(n+1)(-5) |